Evaluation of Pharmacokinetics and Pharmacodynamics of BI 425809, a Novel GlyT1 Inhibitor: Translational Studies. Issue 6 (23rd August 2018) - Rosenbrock, Holger; Desch, Michael; Kleiner, Oliver; Dorner‐Ciossek, Cornelia; Schmid, Bernhard; Keller, Sascha; Schlecker, Christina; Moschetti, Viktoria; Goetz, Sophia; Liesenfeld, Karl‐Heinz; Fillon, Gwenaelle; Giovannini, Riccardo; et al.
Abstract : BI 425809 is a potent and selective glycine transporter 1 (GlyT1) inhibitor being developed for the treatment of cognitive impairment in Alzheimer disease and schizophrenia. Translational studies evaluated the effects of BI 425809 on glycine levels in rat and human cerebrospinal fluid (CSF). Oral administration of BI 425809 in rats induced a dose‐dependent increase of glycine CSF levels from 30% (0.2 mg/kg, not significant) to 78% (2 mg/kg, P  < 0.01), relative to vehicle. Similarly, oral administration of BI 425809 in healthy volunteers resulted in a dose‐dependent increase in glycine CSF levels at steady state, with a mean 50% increase at doses as low as 10 mg. The peak plasma concentration (Cmax ) of BI 425809 was achieved earlier in plasma than in CSF ( t max 3–5 vs. 5–8 hours, respectively). Generally, BI 425809 was safe and well tolerated. These data provide evidence of functional target engagement of GlyT1 by BI 425809.